In situ XPS investigations of Cu1-xNixZnAl-mixed metal oxide catalysts used in the oxidative steam reforming of bio-ethanol - Velu, S.; Suzuki, K.; Vijayaraj, M.; Barman, S.; Gopinath, Chinnakonda S. (Applied Catalysis B - Environmental, 2005)
A series of CuNiZnAl-multicomponent mixed metal oxide catalysts with various Cu/Ni ratios were prepared by the thermal decomposition of Cu1-xNixZnAl-hydrotalcite-like precursors and tested for oxidative steam reforming of bio-ethanol. Dehydrogenation of EtOH to CH3CHO is favored by Cu-rich catalyst. Introduction of Ni leads to C-C bond rupture and producing CO, CO2 and CH4. H-2 yield (selectivity) varied between 2.6-3.0 mol/mol of ethanol converted (50-55%) for all catalysts at 300 degreesC. The above catalysts were subjected to in situ XPS studies to understand the nature of active species involved in the catalytic reaction. Core level and valence band XPS as well as Auger electron spectroscopy revealed the existence of Cu2+, Ni2+ and Zn2+ ions on calcined materials. Upon in situ reduction at reactions temperatures, the Cu2+ was fully reduced to Cu-0. while Ni2+ and Zn2+ were partially reduced to Ni-0 and Zn-0, respectively. On reduction, the nature of ZnO on Cu-rich catalyst changes from crystalline to amorphous, relatively inert and highly stabilized electronically. Relative concentration of the Ni-0 and Zn-0 increases upon reduction with decreasing Cu-content. Valence band results demonstrated that the overlap between 3d bands of Cu and Ni was marginal on calcined materials, and no overlap due to metallic clusters formation after reduction. Nonetheless, the density of states at Fermi level increases dramatically for Ni-rich catalysts and likely this influences the product selectivity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: auger electron spectroscopy; Autothermal reforming; Bio-ethanol; copper oxide; fuel cell; Hydrogen; hydrotalcite; mixed metal oxides; nickel oxide; oxidative steam reforming; Steam reforming; XPS

Selective hydrogenation of furfural to furfuryl alcohol over Pd supported on ternary oxide in aqueous medium under mild conditions - Nehra, Pooja; Betsy, K. J.; Vinod, C. P. (ChemCatChem, 2025)
We report palladium (Pd) supported on a mixed CuO/ZnO/Al2O3 catalyst for the synthesis of furfuryl alcohol (FA) from furfural (FF) using hydrogen under near atmospheric pressure (balloon pressure) conditions. A systematic study of various metal oxide combinations revealed that the best support for Pd nanoparticles is a CuO/ZnO/Al2O3 mixed system, which results in excellent catalytic performance. A series of control experiments highlighted the essential role of mixed Cu-Zn-Al oxide support in facilitating the adsorption and activation of FF. Our results demonstrate that under optimal conditions (40 degrees C, balloon pressure H2), the catalyst yields FF conversion exceeding 98%, with remarkable selectivity for FA reaching up to 99% with water as solvent. The catalyst exhibited almost comparable activity up to three catalytic cycles without extra catalyst treatment or reactivation with negligible Pd leaching. These findings shed insight into the design of mixed metal oxide-based support for active metal interactions in optimizing catalytic performance in furfural hydrogenation under mild conditions.
Keywords: Biomass conversion; Furfural hydrogenation; Furfuryl alcohol; mixed metal oxides; Pd catalyst